How the Class-Advantaged Fail to Obtain Greater Economic Capital from Their Greater Social Capital - Jessi Streib (Socius)
How do class-advantaged individuals with more social capital fail to obtain greater economic capital than class-disadvantaged individuals with less? Although stratification scholars often assume that the class-advantaged convert their greater social capital into greater economic capital, social capital researchers regularly find no wage benefit from its possession or use. Drawing on the case of college students entering the midtier business labor market, this study uncovers how overlooked properties of fields contribute to this phenomenon. Fields that hide information about who can help, how to get ahead, and which jobs pay the most neutralize the class-advantaged’s social capital. In these fields, the class-advantaged do not know whom to ask for help, and without knowledge of how or where to get ahead, their connections often give them ineffective advice and lead them into low-paying as well as high-paying positions. By highlighting the role of hidden information, this study challenges assumptions about the straightforward conversion of social into economic capital and shows how the class-advantaged’s seeming advantages break down.